Pengembangan Media Audio Visual untuk Meningkatkan Keterampilan Proses Sains pada Siswa Kelas IV SDN Kedungwaringin 02 - Raudatul, Raudatul janah; Awalina Barokah (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to develop audiovisual learning media to improve the science process skills of fourth-grade students at SDN Kedungwaringin 02. The background of this research highlights problems in IPAS learning, which is still dominated by conventional methods, resulting in low student participation and underdeveloped science process skills. This development research employed the ADDIE model (Analysis, Design, Development, Implementation, Evaluation) to create the learning media. The product developed was a seven-minute audiovisual graphic video containing material on the introduction of three groups of animals based on their diet. Validation results from material, media, and language experts indicated that the media was highly feasible for use. The effectiveness of the media was measured by comparing students’ pretest and posttest results, with an N-Gain score of 0.73, categorized as high. These findings demonstrate that the use of audiovisual media has a significant impact on enhancing students’ science process skills, particularly in the abilities of observing, classifying, and concluding.